2022
DOI: 10.32493/pjte.v5i2.18596
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kegagalan Laminasi Komposit Epoksi/Serat Karbon Pada Sayap Pesawat Tanpa Awak

Abstract: This study aims to analyze the initial failure value using the Tsai – Wu criteria from the wing skin of an unmanned aircraft with the Eppler 214 airfoil model. The study was carried out using computer modeling with Abaqus software. The material used is an epoxy composite which is carbon fiber. The composites used in the wing skins have two different arrangement sequences, namely the fiber layer arrangement sequence 1 [00/900]8s and the layer sequence 2 [00/+450/-450/900]2s. The load given to the wing is a pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The orientation of the fiber direction greatly determines the strength of the composite relative to the existing stress distribution (Adamy et al, 2020) (Roza & Dirhamsyah, 2015), conducted research with the materials used including coconut fiber powder, sengon wood, urea formaldehyde (UF) binder, 25% emulsion (paraffin) 40% and catalyst (NH4CL) (Roza & Dirhamsyah, 2015). Research on epoxy/carbon fiber composite laminates on unmanned aircraft wings was reported by (Siregar & Arief, 2022). The research of effect of stacking sequence on Charpy impact and flexural damage behavior of composite laminates (Caminero et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The orientation of the fiber direction greatly determines the strength of the composite relative to the existing stress distribution (Adamy et al, 2020) (Roza & Dirhamsyah, 2015), conducted research with the materials used including coconut fiber powder, sengon wood, urea formaldehyde (UF) binder, 25% emulsion (paraffin) 40% and catalyst (NH4CL) (Roza & Dirhamsyah, 2015). Research on epoxy/carbon fiber composite laminates on unmanned aircraft wings was reported by (Siregar & Arief, 2022). The research of effect of stacking sequence on Charpy impact and flexural damage behavior of composite laminates (Caminero et al, 2016).…”
Section: Introductionmentioning
confidence: 99%